2017
DOI: 10.1515/intox-2017-0014
|View full text |Cite
|
Sign up to set email alerts
|

Monotherapy of experimental metabolic syndrome: II. Study of cardiovascular effects

Abstract: Metabolic syndrome belongs to the most important risk factors of cardiovascular diseases. The aim of this study was to investigate changes in cardiovascular system induced by high cholesterol and high fat diet (HCHF) in HTG rats and their influence by a pyridoindole antioxidant – SMe1EC2 (S). The effects of S were compared with those of atorvastatin (A). Male HTG rats were fed HCHF (1% cholesterol + 7.5% lard) for 4 weeks. S and A were administered p.o., 50 mg/kg b.w. Following experimental groups were used: W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Atorvastatin produced effects comparable with SMe1EC2 in the same dosage. It reduced the total numbers of cases of sustained arrhythmia and arrhythmia in the given experiment and produced cardio-protective effects, as in previous research (23,26). Similarly to other statins, atorvastatin is thought to have many benefi cial pleiotropic effects (22,30).…”
Section: Tab 3 Occurrence Of Ventricular Arrhythmia In Animals Amonsupporting
confidence: 55%
See 2 more Smart Citations
“…Atorvastatin produced effects comparable with SMe1EC2 in the same dosage. It reduced the total numbers of cases of sustained arrhythmia and arrhythmia in the given experiment and produced cardio-protective effects, as in previous research (23,26). Similarly to other statins, atorvastatin is thought to have many benefi cial pleiotropic effects (22,30).…”
Section: Tab 3 Occurrence Of Ventricular Arrhythmia In Animals Amonsupporting
confidence: 55%
“…Both atorvastatin and SMe1EC2 exerted cardio protective effects (22,26,31), established most probably by a complex action on numerous mechanisms affecting cell survival, signalling, oxidative and energy metabolism. In addition to lowering high cholesterol levels, atorvastatin treatment can protect patients suffering from metabolic syndrome, impaired lipid metabolism, and established cardiovascular disease from the occurrence of malignant life-threatening arrhythmia (23).…”
Section: Tab 3 Occurrence Of Ventricular Arrhythmia In Animals Amonmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, drugs with anti-inflammatory and anti-oxidative properties could be a right choice for treating cardiovascular complications associated with metabolic syndrome. This occurred in results of Knezl et al ( 2017 ) who found SMe1EC2 to improve functional state of cardiovascular system of HTG rats fed with high-fat and high-cholesterol diet. In our experiments, administration of SMe1EC2 and atorvastatin significantly reduced serum levels of IL-1 and serum concentrations of TBARS.…”
Section: Discussionmentioning
confidence: 90%
“…injection of 100 mg/kg ketamine and 10 mg/kg xylazine, and, in the first series, anticoagulated with heparin (500 IU i.p.). Hearts were explanted and perfused via the aorta at 80 mm Hg with a modified Krebs-Henseleit solution (Farine et al, 2016;Knezl et al, 2017) and gassed with 95% O 2 and 5% CO 2 .…”
Section: Animalsmentioning
confidence: 99%